The Precarity of Peri-urban Resistance - Iswan Kaputra; Prathiwi Widyatmi Putri (PCD Journal, 2020)
In 1997, Kualanamu was chosen as the site of a new airport in North Sumatra. The central government's unilateral decision created new agrarian conflict and complicated the agrarian issues that had plagued the region since the colonial era. The accumulated conflicts and structural issues left local residents in a precarious state as they became integrated into peri-urban society. This article highlights the complexity of the conflict, the agency–institutional–structural relations that underpin it, and peri-urban resistance within the context of urbanisation and its marginalisation of rural communities.